(untitled) (Bangladesh Pharmaceutical Journal, 2023)
The purpose of the present research was to develop a fast and rapidly dissolving polymeric sublingual thin film of vildagliptin due to its simplicity of use as an alternative to oral disintegrating tablets and better compliance for diabetic patients. Nine different formulations (F1-F9) of vildagliptin sublingual films were produced using diverse concentrations of polymer A and plasticizer B by solvent casting method. Several physicochemical properties, including morphological properties, weight variation test, film thickness, folding endurance, surface pH, percentage of moisture loss, in-vitro disintegration test, in-vitro dissolution test, trinocular microscopic imaging of film, differential scanning calorimetry (DSC), FTIR study and content uniformity were evaluated. The ratios of polymer A-plasticizer B were as follows (5:1), (7:1), (7.67:1), (8:1), (8.5:1), (8.67:1, (9.67:1), (10:1), (11:1) which made the film smooth, mechanically strong and easy to peel out. Among all the different formulations, the F1 formulation showed the most significant result concerning in-vitro dissolution (98.95%) in 5 minutes, minimum disintegration time (38 sec.), less film thickness (116.67 ± .58 μm) and better folding endurance (403 times). Bangladesh Pharmaceutical Journal 26(2): 212-218, 2023 (July)